Internet facilities for virtual and hands-on educational experiments - Kalinin, V.; Kazachkov, A.; Novikov, V.; Semenets, V. V.; Семенець, В. В. (University of Cyprus, 2003)
Real time computer simulators of the standard educational Physics laboratory works were designed in VRML and Java for distant learning and self-studies of University students. Experimental schemes and software were developed of educational hands-on computer-based experiments to be performed by High School and University students out of their physical laboratory.
Keywords: virtual laboratory work; distant learning; VRML-simulation; Education in Physics; hands-on computer-based experiments